Citation classics in applied biomechanics of sports - Knudson, D. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
This study documented the top cited research articles, reviews, and books in the biomechanics of sports performance. A systematic search of Scholar Google records for "biomechanics" and at least one of the terms "sport" and "sports" was conducted. Publications focusing on exercise, injury, or basic science were excluded. Over 118,000 records were indexed and the top twenty were ranked by citations. Highly-cited papers were focused on running, throwing, and jumping. There was limited agreement between articles highly cited and those nominated as influential in a previous survey of sports biomechanics scholars, supporting previous concerns about citation counts as a surrogate measure of the importance of scientific publications in applied sports biomechanics.